2023
DOI: 10.21521/mw.6756
|View full text |Cite
|
Sign up to set email alerts
|

Combating tuberculosis in European bison in the Bieszczady Mountains - administrative aspect

Abstract: Tuberculosis in animals is an infectious and contagious disease, caused by acid-fast bacilli of the Mycobacterium tuberculosis complex. The disease has been confirmed in Poland in farm and wild animals. Among the latter the largest number of cases was diagnosed in free-ranging European bison in the Bieszczady Mountains. The disease has also been present there since 2013 in the wild boar population. From April 21, 2021, in accordance with EU Regulation 2016/429, tuberculosis in European bison is a disease that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
1
4
0
Order By: Relevance
“…No bacteria from the MTBC were isolated from the examined samples collected from 76 free-living red and roe deer. These findings are consistent with those of previous studies conducted in the Bieszczady Mountains, where no MTBC infections were found in cervids, apart from a single case of M. caprae infection in a roe deer [14,17].…”
Section: Discussionsupporting
confidence: 93%
“…No bacteria from the MTBC were isolated from the examined samples collected from 76 free-living red and roe deer. These findings are consistent with those of previous studies conducted in the Bieszczady Mountains, where no MTBC infections were found in cervids, apart from a single case of M. caprae infection in a roe deer [14,17].…”
Section: Discussionsupporting
confidence: 93%
“…The European bison (Bison bonasus) is particularly susceptible to Mycobacterium tuberculosis complex (MTBC) infection; indeed, it has been the most common source of bovine tuberculosis mycobacteria isolation in Poland in recent years (Radulski et al 2019). Between 1996 and 2013, 45 cases of tuberculosis were confirmed microbiologically in this species in the Bieszczady Mountains in two different herds (Welz et al 2005). Cases of BTB have also been confirmed in captive European bison, most recently Mycobacterium caprae in the Smardzewice Bison Breeding Center (central Poland) in 2018 (Didkowska et al 2020(Didkowska et al , 2021.…”
Section: Results Analysismentioning
confidence: 87%
“…In addition, the MTC seroprevalence is not significantly different by status and locality. In the case of locality, this is surprising as in previous years, TB was microbiologically confirmed only in two captive herds, namely one herd in Smardzewice, central Poland and another (Wolisko) in Borecka Forest, and in two free‐living herds, namely in the Bieszczady Mountains and Borecka Forest (Krajewska et al., 2011 , 2016 ; Welz et al., 2005 ); therefore, it was anticipated that most positive results would be identified in these locations. In addition, localities with the highest seroprevalence (Białowieża Forest, Bieszczady Mountains, Niepołomice and Pszczyna) are not adjacent to each other (Figure 1 , Table 1 ).…”
Section: Discussionmentioning
confidence: 88%
“…It has been suggested that European bison are highly sensitive to Mycobacterium spp. infections ; indeed, TB has been confirmed in both captive and free-living herds of European bison in Poland (Welz et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation